Becoming-Flashdrive: The Cinematic Intelligence of Lucy. Issue 3 (October 2020) - Kent, Laurence
Abstract : An important but easily forgotten moment in the history of film-philosophy is Jean Epstein's assertion that cinema, more than merely thinking, has a kind of intelligence. If it is a newfound conception of rationality that is needed for any contemporary ethical relation to the world, as thinkers from Reza Negarestani and Pete Wolfendale to feminist collective Laboria Cuboniks have espoused in their respective neo-rationalist projects, then cinema as a thinking thing must be interrogated in its relation to reason. A somatophilia of purely affective and phenomenological approaches in film theory alongside micropolitical injunctions to undermine common-sense and liberate one's desire in extremity can fall limp in view of such calls for universal thinking around rationality. To understand cinema's specific form of intelligence, this article will explore Luc Besson's Lucy (2014) as an instance of how film is able to represent intelligence. Besson's film provides a site where Western cultural anxieties and assumptions around intelligence are manifested. This will allow an explication of contemporary approaches to intelligence in philosophy whilst confronting these discourses with the insidious problematics of gender and race that undergird the film. I argue that Lucy shares many of its ambitions with the emerging vectors of thought associated with the neo-rationalist perspective in its engaging with a rethinking of universal values and the Promethean possibilities of human action. Reading the film through these philosophies will help position the ethical stakes it sets up, but also to distinguish it from a trend of contemporary "posthuman" films that it finds itself in company with. While it is certainly true that posthuman themes, as well as transhumanist fantasies, seem to permeate Besson's film, this article will incorporate another neologism, taken from neo-rationalist thinkers, in order to emphasise moments that can be productive from the standpoint of a philosophical account of intelligence: "rationalist inhumanism."